2016
DOI: 10.1002/polb.24267
|View full text |Cite
|
Sign up to set email alerts
|

Anion conducting methylated aliphatic PBI and its calculated properties

Abstract: A methylated polybenzimidazole with an aliphatic chain in the backbone (Me‐PBI‐C10) was synthesized and formed into membranes. Literature suggests that alkyl chains on C2 of imidazolium ions increase their alkaline stability. While this may be true for model compounds or ions attached as a side chain, both our DFT calculations and experimental results show that Me‐PBI‐C10 does not withstand alkaline conditions. To increase the alkaline stability, blend membranes with PBI‐OO were fabricated. A blend membrane wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…Because the nickel complex had a smaller Δ H tot , but likely a similar T Δ S term, the Δ G of counterion exchange for the nickel complex was more negative than for the other metals, suggesting that there was more of a thermodynamic driving force for chloride ion release, a parameter that has previously been difficult to measure for AEMs and PEMs. Additionally, the lower Δ H tot indicated that less energy needed to be absorbed by the nickel system to facilitate counterion exchange, strongly suggesting that nickel had weaker initial binding to its chloride counterion . Weaker initial counterion binding and a stronger thermodynamic driving force for counterion release should increase the number of free ions and increase the AEM’s conductivity. , Given that ion release is critical to any conductivity mechanism, and that the percentage of free ions is directly correlated to conductivity, this thermodynamic driving force for ion release appears to be the prevailing factor for the nickel-based AEM’s superior ion conductivity. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the nickel complex had a smaller Δ H tot , but likely a similar T Δ S term, the Δ G of counterion exchange for the nickel complex was more negative than for the other metals, suggesting that there was more of a thermodynamic driving force for chloride ion release, a parameter that has previously been difficult to measure for AEMs and PEMs. Additionally, the lower Δ H tot indicated that less energy needed to be absorbed by the nickel system to facilitate counterion exchange, strongly suggesting that nickel had weaker initial binding to its chloride counterion . Weaker initial counterion binding and a stronger thermodynamic driving force for counterion release should increase the number of free ions and increase the AEM’s conductivity. , Given that ion release is critical to any conductivity mechanism, and that the percentage of free ions is directly correlated to conductivity, this thermodynamic driving force for ion release appears to be the prevailing factor for the nickel-based AEM’s superior ion conductivity. , …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the lower ΔH tot indicated that less energy needed to be absorbed by the nickel system to facilitate counterion exchange, strongly suggesting that nickel had weaker initial binding to its chloride counterion. 61 Weaker initial counterion binding and a stronger thermodynamic driving force for counterion release should increase the number of free ions and increase the AEM's conductivity. 1,49 Given that ion release is critical to any conductivity mechanism, and that the percentage of free ions is directly correlated to conductivity, this thermodynamic driving force for ion release appears to be the prevailing factor for the nickel-based AEM's superior ion conductivity.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…313 Another attempt to improve the stability was to incorporate longer aliphatic segments in the structure (Table 1; Entry 9), but the concept did not circumvent the major degradation mode. 98 A more effective stabilization approach was reported by Thomas et al, 90 who introduced methyl substituents on the m-phenylene group adjacent to the polybenzimidazolium C2 position (see Table 1; Entry 6). After N-methylation, as shown in Scheme 9, the dihedral angle between the benzimidazoliums and the phenylenes was changed so that the methyl groups on the phenylene moieties were positioned above and under the benzimidazolium plane and sterically protected the benzimidazolium C2 position from nucleophilic attack.…”
Section: Poly(dialkyl Benzimidazolium)smentioning
confidence: 99%
“…A hybrid B3LYP functional method along with 6–311 G** basis set was used for geometry optimization and frequency calculations of all the species, 16 and the natural charge was analyzed by natural bond orbital. Another major goal of this investigation was to calculate enthalpy (∆ H ) and Gibb's free energy (∆ G ) of photooxidation of PVC under 1 atm and 298.15 K. An oligomer containing four repeated units for PVC 12 and one structure unit for PBI were selected as the model compound 17 …”
Section: Methodsmentioning
confidence: 99%